1996
DOI: 10.1002/crq.3900140206
|View full text |Cite
|
Sign up to set email alerts
|

The role of children in mediation

Abstract: In spring 1995, a six‐page questionnaire on the topic of including or excluding children in mediation was mailed to all 630 practitioner members of the Academy of Family Mediators. Overall, 51 percent returned the survey. Of those responding, 31 percent were attorneys, 46 percent had graduate‐level mental health backgrounds, and an additional 7 percent had both legal and mental health backgrounds. The survey revealed that 77 percent of respondents included children, either following settlement to discuss the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…The first element of MEDUC's definition of family mediation is child‐inclusive practice (CIP) 2 . Even though the concept of family mediation first appeared in the USA in 1970 in The Bridge Project, which worked with runaway children and their parents in Atlanta (Brown, 1982), objections and reservations to the involvement of children in mediation later prevailed (Cashmore & Parkinson, 2009; Garwood, 1990; Lansky et al, 1996). Available studies at the time showed that children were involved in less than half of all mediations in the long term, with the median of comparison between studies in the area of around 20% of cases (Drapkin & Bienenfeld, 2012; Saposnek, 2004).…”
Section: Child‐inclusive Mediation Centrementioning
confidence: 99%
See 1 more Smart Citation
“…The first element of MEDUC's definition of family mediation is child‐inclusive practice (CIP) 2 . Even though the concept of family mediation first appeared in the USA in 1970 in The Bridge Project, which worked with runaway children and their parents in Atlanta (Brown, 1982), objections and reservations to the involvement of children in mediation later prevailed (Cashmore & Parkinson, 2009; Garwood, 1990; Lansky et al, 1996). Available studies at the time showed that children were involved in less than half of all mediations in the long term, with the median of comparison between studies in the area of around 20% of cases (Drapkin & Bienenfeld, 2012; Saposnek, 2004).…”
Section: Child‐inclusive Mediation Centrementioning
confidence: 99%
“…Nevertheless, since the late 1980s, rather protective discourses preventing the involvement of children in mediation have gained ground (Cashmore & Parkinson, 2009; Clulow & Vincent, 1987; Collinson & Gardner, 1990; Davidson, 1987; Garwood, 1990; Lansky et al, 1996; Warshak & Santrock, 1983). “ In conclusion, it was argued that the disadvantages of involving children directly or indirectly in the mediation process far outweighed any advantages .” (Roberts, 2008, p. 195).…”
Section: Child‐inclusive Mediation Centrementioning
confidence: 99%
“…(Hart, 1990 ;Grillo, 1991 ;Benjamin et Irving, 1992 ;Johnson et al, 2005 ;Murphy et Rubinson, 2005 ;Holtzwoth-Munroe, 2011 ;Rivera, Sullivan et Zeoli, 2012) En ce qui a trait à la sécurité des enfants, il est à noter que dans Guide des normes de pratique en médiation familiale (COAMF, 2016), il n'y a pas de section qui aborde les pratiques à adopter pour assurer la sécurité des enfants. D'ailleurs, jusqu'à présent, peu d'études 7 se sont intéressées à l'implication des enfants en médiation familiale (Achim et al, 1997 ;Lansky et al, 1996 ;Richard, 2014), notamment lorsqu'il y a présence de violence conjugale. La décision d'impliquer les enfants ou non dans le cadre du processus de médiation familiale revient au médiateur familial (Achim et al, 1997).…”
Section: Débats Entourant La Définition De La Violence Conjugaleunclassified
“…Afin de faire ce choix, le médiateur familial doit d'abord bien connaître les parents, de même que la situation familiale (notamment le niveau des conflits parentaux, l'hostilité et la faible coopération entre les parents) afin de déterminer s'il est approprié d'impliquer les enfants (Richard, 2014). Après tout, il s'agit de sa responsabilité d'agir avec prudence, d'assurer la sécurité des enfants et de contrôler les risques associés à leur implication directe en médiation familiale (Achim et al, 1997 ;Lansky et al, 1996 ;Richard, 2014). Nous estimons que des recherches futures devraient porter spécifiquement sur les enjeux et les dangers liés à l'implication des enfants en médiation familiale lorsqu'il y a présence de violence conjugale.…”
Section: Débats Entourant La Définition De La Violence Conjugaleunclassified